2010
DOI: 10.1007/s11084-010-9224-z
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Manganese-Calcium Oxides as a Possible Evolutionary Origin for the CaMn4 Cluster in Photosystem II

Abstract: In this paper a few calcium-manganese oxides and calcium-manganese minerals are studied as catalysts for water oxidation. The natural mineral marokite is also studied as a catalyst for water oxidation for the first time. Marokite is made up of edge-sharing Mn(3+) in a distorted octahedral environment and eight-coordinate Ca(2+) centered polyhedral layers. The structure is similar to recent models of the oxygen evolving complex in photosystem II. Thus, the oxygen evolving complex in photosystem II does not have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 34 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…This natural process is the most efficient known, for the photo-generation of H 2 from water. Among many calcium manganese oxides, CaMn 2 O 4 contains structural sub-units of (Mn 4 CaO x ), similar to the structure of natural CaMn 4 O 5 cluster in OEC [5,6]. This has led to extensive investigation of catalytic water oxidation properties of CaMn 2 O 4 [7][8][9].…”
Section: Introductionmentioning
confidence: 98%
“…This natural process is the most efficient known, for the photo-generation of H 2 from water. Among many calcium manganese oxides, CaMn 2 O 4 contains structural sub-units of (Mn 4 CaO x ), similar to the structure of natural CaMn 4 O 5 cluster in OEC [5,6]. This has led to extensive investigation of catalytic water oxidation properties of CaMn 2 O 4 [7][8][9].…”
Section: Introductionmentioning
confidence: 98%
“…From a simple view on the chemical evolution, [23–32] which could be extended to a useful conception, it can be imagined that among many metal ions around the apo‐enzyme of photosystem II and under the OER conditions, Ca and Mn ions were selected and used to finally construct the OEC [28–32] . Recently, Dau's group showed that photosystem II can efficiently form layered Mn oxide particles under photochemical reaction, even in the absence of specific protein subunits [32] …”
Section: Introductionmentioning
confidence: 99%
“…Mn oxides were reported as water-oxidizing catalysts for artificial photosynthetic systems [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Among Mn oxides, nanolayered Mn oxides with different organic or inorganic ions between layers are efficient and stable in water oxidation [41].…”
Section: Introductionmentioning
confidence: 99%